The rebels of Ireland the Dublin saga - Rutherfurd, Edward 1948- (Doubleday, 2006)
Once again Rutherfurd takes us inside the process of history by tracing the lives of several Dublin families from all strata of society, Protestant and Catholic, rich and poor, conniving and heroic.
Keywords: Geschichte 1597-1920; Geschichte; Irland; Dublin (Ireland) -- Fiction; Ireland -- History -- 1172- -- Fiction; Fiktionale Darstellung; Historical fiction